POLA KEPEMIMPINAN ISLAMI ORANG TUA DALAM KELUARGA: MENUJU PENGEMBANGAN PENDIDIKAN KARAKTER ISLAMI BAGI GENERASI MUDA MASA DEPAN - Ikhlasul Amal Pasaribu; Poltak Gultom; Elysa Tanjung (JIP: Jurnal Ilmu Pendidikan, 2023)
This research explores the Islamic leadership patterns implemented by parents within the family context, aiming to foster the development of Islamic character education for future generations. Through qualitative research methods, we analyze the behaviors, values, and Islamic leadership strategies employed by parents in the family education context. The findings of this research identify key factors supporting the development of Islamic character in children, providing valuable insights for efforts to enhance Islamic character education from a family perspective. The research aims to contribute to both practical and theoretical understanding of the role of parents in shaping the Islamic character of the younger generation, aligning with the vision of sustainable character education development.